ESTIMASI LAJU EROSI/DEPOSIT PADA LAHAN OLAHAN KECIL DI PUNCAK-BOGOR DENGAN ISOTOP ALAM 137Cs - Nita Suhartini (Purifikasi, 2007)
Investigation of the erosion rate estimation had been done using environmental isotope 137Cs. Radiogenic 137Cs contents of the soil can be used to estimate the amount of erosion/deposition in an area that has been occurring since the late 1950’s, with respect to the stable reference site. The investigation aimed to estimate erosion/deposit rate in small cultivated site that using ridge and furrow system located in Puncak - Bogor. Sampling of soil was done by using scraper (20 x 50) cm for reference site, and coring (Φi = 7 cm) for investigation points. Two small cultivated sites were chosen namely TS3 (50 x 60) m, and TS5 (50 x 60) m. The result showed that net erosion for TS3 and TS5 were -5 ton/ha.year and -39 ton/ha.year, respectively.